Pengrajin Batik Dan Hak Kekayaan Intelektual: Studi Tentang Perlindungan Hukum Terhadap Pembajakan Hak Cipta Batik Di Kampung Laweyan Surakarta - Hutomo, Arief Rahman Priyo, Kelik Wardiono, S.H., M.H., Cd.Dr, Inayah, SH., M.H (2014)
The purpose of this study are: 1) To describe patterns and explain the pattern of copyright infringement by batik craftsmen in Kampung Laweyan Surakarta. 2) To describe and explain the legal protection for batik craftsmen as the owners of copyright in Kampung Laweyan Surakarta whom their copyrights are infringed. From the analysis results of the research, it is obtained conclusion that patterns of copyright infringement by Batik craftsmen in Kampung Batik Laweyan Surakarta is batik motives and brand plagiarism. This infringes the provisions of Article 12 and Article 72 paragraph (2) of Law No. 19 of Year 2002 about piracy. Legal protection for batik craftsmen as the owner of copyright in Kampung Surakarta Laweyan Surakarta is conducted by copyright registration and forming community among batik craftsmen . The efforts that performed by Batik craftsmen in Kampung Batik Surakarta Laweyan to protect copyright infringed is by change batik motives once in three months.